Separation and recovery of phenols from an aqueous solution by a green membrane system. (1st April 2020) - Mei, Xiang; Li, Junhui; Jing, Chenchen; Fang, Chenhong; Liu, Yang; Wang, Yong; Liu, Juan; Bi, Shuqi; Chen, Ying; Xiao, Yanyan; Yang, Xu; Xiao, Yifan; et al.
Abstract: Oil-refinery alkali residue wastewater (ORARW) contains large amounts of phenol and its derivatives, which are highly toxic and valuable but difficult to biodegrade. In this study, using vegetable oil as the liquid membrane phase, a green polypropylene-hollow-fiber supported liquid membrane (SLM) system was constructed to simultaneously separate and recover phenol, m -cresol and o -cresol from aqueous solutions. After screening several types of vegetable oil, linseed oil was selected as the liquid membrane phase. Based on a single SLM module and using a NaOH solution as the stripping reagent with feed phase and stripping phase hydraulic retention times (HRTs) of 7.8 and 6.9 min, respectively, the phenol separation and recovery rates were 92.9% and 88.8%, respectively. The separation rates for m -cresol and o -cresol were both greater than 96%, their recovery rates were approximately 92%, and the membrane separation flux of every phenolic compound exceeded 0.40 g/m 2 ·h. When two SLM modules were operated in series at room temperature for 3 h, the separation efficiency for phenols increased by approximately 9% compared with that obtained with a single SLM module. After applying two SLM modules in series to treat ORARW with an initial concentration of phenols of 4800–5200 mg/L, the simultaneous separation and recovery rates of phenols were near 95% and 92%, respectively. This work concluded that vegetable oil can be used as a nontoxic and renewable green liquid membrane phase and that two SLM modules in series efficiently separated and recovered phenols from aqueous solutions. Graphical abstract: Image 10784 Highlights: Vegetable oil was used as an SLM liquid membrane to separate and recover phenols. The order of the phenol extraction was linseed oil > sunflower oil > rapeseed oil. Two membrane modules in series were more effective for the separation of phenols. The separation and recovery rates for phenols reached 95% and 92%, respectively. The SLM system can be used in an oil refinery as a cleaner production process.